A Critical Evaluation of the Hotel Classification System of India - Sufi, Tahir; Singh, Satinderpal (Prabandhan: Indian Journal of Management, 2019)
A hotel classification system is a tool used to create a hierarchy of hotels based on service quality. However, there is a lot of criticism in literature against the system for allocating high ratings to hotels with poor service quality, micro managing hotels, charging high license fees for hotels that opt for classification, etc. Against the backdrop of this criticism for the classification system, this study explored the perceptions of hotel managers about the system. The study also identified the reasons for a large number of hotels not opting for the classification process inspite of several benefits claimed by the Ministry of Tourism under the scheme. Finally, the study identified the changes hotels make to get the desired star rating. Using a multi-stage stratified sampling technique, data were collected through a structured questionnaire from 205 hotel managers of classified and unclassified hotels in North India using Google Docs questionnaire. The study was conducted in March 2017. The data were analyzed using SPSS software. Descriptive statistics and factor analysis tests were used for the analysis. The results indicated that managers had a positive opinion about the classification process contrary to what is discussed in the literature. The study also revealed that the barriers that prevent hotels from applying for the classification process include the requirement of higher salaries, a large number of approvals, high license fees, and huge documentation. Finally, the study revealed that for getting the desired classification, hotels should make changes like improving the quality of dÃ©cor in rooms, placing superior guest room amenities, providing superior furnishings, and recruitment of professional employees.